The Dynamics of Indian Federalism: A Legal Analysis - Mallikarjun M. Ambli, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Federalism in India has undergone significant transformation since its inception, influenced by constitutional amendments, judicial pronouncements, political dynamics, and economic reforms. The evolving nature of Indian federalism reflects the changing balance of power between the Union and the states, driven by administrative restructuring, fiscal federalism, and regional aspirations. While the Constitution of India establishes a quasi-federal structure, recent trends indicate a shift toward a more centralized approach, raising concerns over state autonomy and cooperative federalism. This paper critically examines the evolving dimensions of Indian federalism, focusing on legal frameworks, case laws, and policy changes that shape its trajectory. It also explores the impact of key legislations and governance models on the federal structure, addressing challenges such as fiscal imbalances, inter-state disputes, and the role of regional parties. By analyzing recent developments, this study aims to contribute to the discourse on India’s federal identity and the need for a more balanced and inclusive approach to federal governance.
Keywords: Federalism; Constitution; Autonomy; Cooperative; Judicial Interpretations